Marqueurs cadratifs temporels et argumentatifs dans les récits d’apprenants néerlandophones de français L2 - Aurélie Welcomme (Discours)
This paper proposes a quantitative corpus-based study investigating the presence of temporal framing and argumentative markers in the narrative monologues of Dutch-speaking learners of French as a second language. The narrative texts were collected from Dutch-speaking monolinguals from two contexts (Flanders and Brussels) and at two different stages of their learning curriculum (1st and last year of secondary education). Ten subjects from each group were asked to tell a wordless picture-book story (Frog Story, Mayer, 1969). The production of temporal framing and argumentative markers in these narratives has been compared to that of groups of native speakers of the same age and curricular level. We hypothesized that the amount of curricular and extracurricular contact would influence the production of temporal framing and argumentative markers. The results are not straightforward: more contact with French as an L2 seems to influence learners’ performance differently, and we do not always find a significant difference with the native speaker groups.